2006
DOI: 10.1111/j.1365-2516.2006.01179.x
|View full text |Cite
|
Sign up to set email alerts
|

Deep vein thrombosis in a patient with severe haemophilia A

Abstract: A 25-year-old male with severe haemophilia A developed deep vein thrombosis of the left upper limb. Venography showed thrombosis of the basilic vein. There was no underlying prothrombotic condition. He was successfully treated with low-molecular weight heparin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 10 publications
(25 reference statements)
0
14
0
2
Order By: Relevance
“…Only a handful of cases of spontaneous VTE in (untreated) hemophilia have been reported in the literature. 22,23 Spontaneous VTE is also rare in patients with VWD: in a recently published review of 486 VWD patients at a single institution, for instance, there were no cases of venous thrombosis. 24 A literature review within the same publication reported 33 cases of VWD and venous thrombosis, with all but 7 cases having identifiable risk factors; the most common risk factor (N 5 14) was factor replacement therapy consisting of VWF with FVIII.…”
Section: Vte In Bleeding Disordersmentioning
confidence: 99%
“…Only a handful of cases of spontaneous VTE in (untreated) hemophilia have been reported in the literature. 22,23 Spontaneous VTE is also rare in patients with VWD: in a recently published review of 486 VWD patients at a single institution, for instance, there were no cases of venous thrombosis. 24 A literature review within the same publication reported 33 cases of VWD and venous thrombosis, with all but 7 cases having identifiable risk factors; the most common risk factor (N 5 14) was factor replacement therapy consisting of VWF with FVIII.…”
Section: Vte In Bleeding Disordersmentioning
confidence: 99%
“…Other risk factors can be listed as congenital prothrombotic condition in heterozygote level, deficiency of protein C and Factor V Leiden [8]. In addition to these, Kashyap et al .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these, Kashyap et al . have shown that FII G20210A mutation is another risk factor [8]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without VTE prophylaxis, 60% of patients with normal haemostatic systems undergoing major orthopaedic surgery develop a postoperative VTE [50]. Although symptomatic venous thrombosis or pulmonary embolism has been described in patients with haemophilia without inhibitors, there is little information on clinical incidence or prevention [51][52][53][54][55][56]. Although limited in sample size, a 10% incidence of subclinical deep vein thrombosis (DVT), diagnosed by ultrasound, was reported among 20 haemophilia patients without inhibitors undergoing 29 major orthopaedic surgeries [57].…”
Section: Venous Thromboembolism Prophylaxis Following Major Surgerymentioning
confidence: 99%